2000
DOI: 10.1111/1467-3435.00016
|View full text |Cite
|
Sign up to set email alerts
|

Higher Education and Graduate Employment in France

Abstract: Compared to other European higher education systems, the French one seems more complex. Indeed, it juxtaposes a huge, mainly open, university sector and a myriad of schools and institutes with generally limited access. The university sector is itself rather complex, since it is not organised around a clearly defined first degree. There exist different layers of diplomas which follow each other without any explicit exit level. The university sector also has an official role in preparing students for the competi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
4

Year Published

2003
2003
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 1 publication
0
19
0
4
Order By: Relevance
“…Data gathering was done with the help of national and international conferences, often undertaken in cooperation with other institutions (Teichler, 1979;Brennan, Kogan, and Teichler, 1995). In addition, scholars were invited to write trend reports (Kehm and Teichler, 1995) or detailed accounts of available research (Holtkamp and Teichler, 1983;Burkhardt, Schomburg, and Teichler, 2000;Paul, Teichler, and Van der Velden, 2000) as well as synthesizing analyses (Teichler and Sanyal, 1982;Teichler, 1988Teichler, , 1999aTeichler, , 1999bTeichler, , 1999cTeichler, , 2003. This national and international effort yielded valuable information for researchers and practitioners and informed the center's research plans.…”
Section: The Range Of Projectsmentioning
confidence: 99%
“…Data gathering was done with the help of national and international conferences, often undertaken in cooperation with other institutions (Teichler, 1979;Brennan, Kogan, and Teichler, 1995). In addition, scholars were invited to write trend reports (Kehm and Teichler, 1995) or detailed accounts of available research (Holtkamp and Teichler, 1983;Burkhardt, Schomburg, and Teichler, 2000;Paul, Teichler, and Van der Velden, 2000) as well as synthesizing analyses (Teichler and Sanyal, 1982;Teichler, 1988Teichler, , 1999aTeichler, , 1999bTeichler, , 1999cTeichler, , 2003. This national and international effort yielded valuable information for researchers and practitioners and informed the center's research plans.…”
Section: The Range Of Projectsmentioning
confidence: 99%
“…Nevertheless, most of these focus on particular countries. Such studies include: Jones et al (1987) and Woodley & Brennan (2000) for the UK; Plumper and Schneider (2007) and Schomburg (2000) for Germany; Paul and Murdoch (2000) for France; Moscati and Rostan (2000) for Italy; Gines et al (2000) for Spain ;Cardoso and Ferreira (2008) for Portugal; and Livanos (2009) for Greece.…”
Section: Introductionmentioning
confidence: 99%
“…They want adaptable people, people who can use their abilities and skills to make the organisation evolve through bright ideas and persuading colleagues to adopt new approaches and they want transformative employees, people who can anticipate and lead change, who have higher level skills, such as analysis, critique, synthesis, etc (Woodley & Brennan 2000). Similarly, other studies showed that employers generally look for the following in graduates: knowledge -general and business related -, technical know-how in the field of communication, personal skills, flexibility and ambition in France (Paul & Murdoch 2000); specialised competence, methodological competence, social competence and participatory competence in Spain (Mora, Garcia-Montalvo & GarciaAracil 2000); and work attitudes, knowledge, social skills and instrumental skills in Netherlands (Allen, Boezerooy, de Weert & van der Velden 2000).…”
Section: Discussionmentioning
confidence: 99%
“…We can mention the recent studies conducted in a number of European countries: in France by Paul & Murdoch (2000), in Germany by Schomburg (2000), in Italy by Moscati & Rostan (2000), in Norway by Arnesen (2000), in Austria by Kellermann & Sagmeister (2000), in UK by Woodley & Brennan (2000) and others. These studies analysed mainly the relationship between higher education and employment in statistical terms, but also in qualitative terms through aspects such as the abilities and skills graduates need in order to integrate into the labour market.…”
Section: Introductionmentioning
confidence: 96%